ADVERSE DRUG REACTION MONITORING AMONG HYPERTENSIVE PATIENTS OF TERTIARY CARE CENTER OF NORTH INDIA RELATED TO ANTIHYPERTENSIVE DRUGS - MISHRA, SEEMA; AHMAD, SYED S; NIGAM, NILAM; SHANKAR, PRATAP; KUMAR, SHRAVAN; KUMAR, VINAY; GUPTA, SHALINI (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The objective of the study was to monitor the adverse drug reactions (A.D.Rs.) associated with antihypertensive drugs. Methods: All patients coming to the department with blood pressure systolic above 120 mmHg and diastolic above 90 mmHg and prescribed hypertensives will be screened for the study. Results and Discussion: A total of 136 patients were observed during the study. Out of 136 patients, 23 (17%) A.D.Rs. were recorded. A study conducted by Ramesh et al. in the Indian capital reports that 22.3% of the patients experienced A.D.Rs. Conclusion: Furthermore, any appearance of A.D.Rs. due to side effects of the drugs or due to bad control and patients non-compliance, it was treated mainly by decreasing the doses of the drugs, switching them to another active substance from the same pharmacological group, or by adding more active substances from different pharmacological groups in lower dosages to achieve the B.P goals.